Bioactives in Disease Prevention and Health Promotion: Exploiting Combinatorial Effects - Gurumallu, Sunil C.; Javaraiah, Rajesha (Current Bioactive Compounds, 2021)
Background: Many bioactive molecules, such as lycopene, resveratrol, lignan, tannins, indoles, fatty acids, etc., found in small amounts in plants, animals, and micro-organisms have been extensively investigated for their diverse preventive, therapeutic, immune-modulating and toxicological effects. Currently, the growing interest of the consumers is shifted towards a novel bioinspired strategy of cocktailing two or more bioactives at a lower concentration to reduce both side and cost effects, and to enhance positive effects for the development of novel compounds by the food, pharmaceutical, and chemical industries. Methods: Even though there are several regularly updated and published reports showing the importance of beneficial effects of bioactives individually, no systematic reviews are outlining how the bioactives have combinatorially acted together to provide such health benefits and disease preventive effects. Hence, various electronic scientific databases, such as Pub Med, Science Direct, Google scholar, Sci-Finder were searched to collect the data of the present review. Results: One hundred and sixty-two research and review papers collected from peer-reviewed journals are cited in the present review covering the broad spectrum of many bioactives and their importance in the field of food, feed, and drug industries. Conclusion: The present systematic review discusses and highlights the current knowledge on the concept of synergistic and combinatorial effects of various bioactives from the plant, animal, micro- organism sources, and synthetic drugs in disease prevention and health promotion. These findings may pave a way for the discovery of new bioactive products and process development, which could add to economic importance.
Keywords: bioavailability